Optimization of nucleosome assembly from histones and model DNAs and estimation of the reconstitution efficiency - Kutuzov, M.M.; Kurgina, T.A.; Belousova, E.A.; Khodyreva, S.N.; Lavrik, O.I. (Вiopolymers and Cell, 2019)
Nucleosome core particles (NCPs) are basic units of chromatin organization; they represent the most convenient model system for the study of key DNA-dependent processes. Therefore, a robust method of nucleosome assembly is important for research. To prepare NCPs, purified histones and DNAs with sequences providing strong positioning of DNA relative to histone octamer are commonly used, and a method to control the efficacy of NCP reconstruction is required. Aim. To optimize the procedure for NCP reconstitution from purified histone octamers and different types of synthetic model DNAs and develop a new approach for express analysis of the efficacy of NCP reconstitution. Methods. Dialysis, PAAG, fluorescence measurement using the Eva-Green dye. Results. We first developed a convenient procedure for NCP assembly in a low-salt buffer with a variable DNA-histone ratio at the first stage. Once the optimal ratio was determined, NCPs could be assembled by a slow gradient dialysis. The efficacy of NCP assembly can be estimated directly in the solution using the Eva-Green dye. Conclusions. The efficacy of dye intercalation into DNA duplex was sharply reduced in the nucleosomal context. The main benefits of the proposed approach are the rapid analysis directly in the solution and possibility to use DNAs without any special tags.